Identifikasi Perilaku Jujur pada Siswa Kelas XII IPA SMA - Arin Rohmahtika; Ricky Purnama Wirayuda (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: Honest behavior is one of the positive behaviors that every individual needs to have from an early age. This study aims to analyze the honest behavior of students in learning Physics, especially the material of heat and its transfer at SMA Negeri 7 Jambi City. Methodology: This research design uses a descriptive type, where the researcher describes the honest attitude of students. This research was at Senior High School 7 in Jambi City. The population in this study were all students of class XII IPA SMA Negeri 7 Jambi City with a total of 60 respondents. Main Findings: From the results of identifying the attitude of honesty in class XII IPA students at Senior High School 7 in Jambi City based on the parameters that have been explained that the character level of honest behavior of class XII IPA students of Senior High School 7 in Jambi City is in the â€œGoodâ€ category. Novelty/Originality of this study: After the research was carried out, it was found that this research was updated, namely being able to find out how the attitude of honesty of class XI I students, especially at Senior High School 7 in Jambi city.